PSEUDOMONAS AERUGINOSA DRUG-RESISTANT ISOLATES IN ICU PATIENTS WITH A SPECIAL PROFILE RELATED TO B-LACTAMASE - Kumar, Rajesh; Gupta, Deepali; H Bhat, Sanjeev (Asian Journal of Pharmaceutical and Clinical Research, 2023)
Objective: In addition to assessing the phenotypic development of biofilms and beta-lactamases, in the current study, Pseudomonas aeruginosa isolates from intensive care units (ICU) patients with prevalent drug resistance are being evaluated. Methods: Standard CLSI recommended protocols were utilized to detect beta-lactamases such as extended-spectrum β-lactamases (ESBL), metallo beta-lactamase (MBL), and AmpC, and a standard tissue culture plate method was used to detect the development of biofilms in the study. Results: 51 (36% of 142) Most P. aeruginosa isolates with multidrug resistance (MDR) phenotypes were discovered in endotracheal aspirates, followed by BAL fluid, pus, and blood, and the least number were found in urine samples. Of the 142 isolates of P. aeruginosa, 132 (93%) produced biofilms, while the remaining 10 (7%) did not. Our study reported that of the 51 MDR isolates, 14 (27%) produced ESBLs, 9 (18%) MBLs, and 5 (10%) AmpCs. Of the 51 MDR phenotypes, 48 (94%) of the isolates produced biofilm, and 3 (6%) did not. There were 142 clinical isolates of P. aeruginosa, 14 (27%) of which came from female patients, and 37 (73%) from male patients. Imipenem (10.4%) and meropenem (12.5%) showed the lowest rates of resistance, whereas gentamicin (60.4%) and amikacin (66.6%) had the greatest rates. There was no resistance to colistin or polymyxin B. Conclusion: For the best antibiotic choice and management of acute disease in ICU patients, all P. aeruginosa bacterial isolates should undergo routine beta-lactamase profiling and biofilm formation.